Worship as Missional Practice - Cronshaw, Darren (Ecclesial practices, 2014)
The corporate worship gathering has been centrally important to Vineyard Churches, but the Emerging Missional Church (emc) movement has challenged them to reconsider how corporate worship interfaces with mission. A linked series of case studies of three Australian Vineyard churches identifies several functions of the Sunday worship gathering. Worship is a ‘centripetal embrace’ for God’s people; which brings focus, community, continuity and a climax to the week. But worship as missional practice is equally about centrifugal release and the need for encouragement, equipping, empowering, direction and missional impetus. These functions are consistent with James Smith’s appeal for worship that forms disciples whose desires are shaped towards the Kingdom of God and whose imaginations are captured with a vision for being actors in God’s story.